Prescription analysis of hypolipidaemic agents in the department of cardiology in a tertiary care hospital - Gari, Manju; Bansal, Megha (International Journal of Basic & Clinical Pharmacology, 2019)
ABSTRACT Background: The objective of the present study was to evaluate the prescribing pattern of hypolipidaemic drugs in the outpatient department of cardiology in a tertiary care hospital. Methods: A cross-sectional study was conducted in the department of cardiology for the period of 3 months. A total of 526 prescriptions were analyzed for variants such as the disease patterns, the type of hypolipidaemic drugs which are prescribed for those diseases, the prescribing daily dose of the hypolipidaemic drugs and the prescribing daily dose/daily defined dose ratio of the drugs. Results: On evaluation of the prescriptions, it was conferred that both the patients of normal lipid profile (34.77%) and abnormal lipid profile (65.18%) were prescribed hypolipidaemic drug. Diabetes with hypertension (35.74%) was the most common disease for which hypolipidaemic drugs were prescribed. Atorvastatin (30.98%) was the most common drug which was prescribed as monotherapy, whereas atorvastatin with aspirin and clopidogrel (17.49%) was the most common drug prescribed in combination. Conclusions: Use of statin has become very prevalent with increasing trends of use in both normal and abnormal lipid profile patients, suggesting consideration of rational use of statins to follow good prescribing pattern so that morbidity and mortality can be prevented.